Pengaruh Ekspektasi Pendapatan, Lingkungan Keluarga dan Efikasi Diri Terhadap Minat Berwirausaha Mahasiswa - syahadati; Sri Arita (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of income expectations, family environment and self-efficacy on the entrepreneurial interest of students of the Faculty of Economics and Business, Padang State University. This type of research is associative. The population in this study were students of the Faculty of Economics and Business, Padang State University. From a total population of 1,336 students, a sample of 93 participants was drawn using Proportional Random Sampling. The primary data in this study were collected by distributing questionnaires to selected students. The analysis technique used is multiple linear regression analysis using SPSS 25. The results of this study indicate that (1) income expectations, family environment, and self-efficacy have a simultaneous influence on students' interest in entrepreneurship, 2) income expectations have a significant influence on students' interest in entrepreneurship, 3) family environment has a significant influence on students' interest in entrepreneurship, 4) self-efficacy does not have a significant influence on students' interest in entrepreneurship.